2010
DOI: 10.1002/bit.22837
|View full text |Cite
|
Sign up to set email alerts
|

The effect of carbon source on microbial community structure and Cr(VI) reduction rate

Abstract: In the present work, the effect of the carbon source on microbial community structure in batch cultures derived from industrial sludge and hexavalent chromium reduction was studied. Experiments in aerobic batch reactors were carried out by amending industrial sludge with two different carbon sources: sodium acetate and sucrose. In each of the experiments performed, four different initial Cr(VI) concentrations of: 6, 13, 30 and 115 mg/L were tested. The change of carbon source in the batch reactor from sodium a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0
6

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 57 publications
1
13
0
6
Order By: Relevance
“…Many factors affect the rate and the extent of microbial Cr(VI) reduction such as the initial biomass concentration, initial Cr(VI) concentration, pH, temperature, oxidation-reduction potential and metal cations (Wu et al, 2010;Ye et al, 2010). Also the presence of suitable carbon source is necessary to enhance the Cr(VI) reduction capacity (Tekerlekopoulou et al, 2010). Similar observations were also referred in previous studies by Ferro Orozco et al (2010) and Contreras et al (2001).…”
Section: Introductionsupporting
confidence: 51%
See 2 more Smart Citations
“…Many factors affect the rate and the extent of microbial Cr(VI) reduction such as the initial biomass concentration, initial Cr(VI) concentration, pH, temperature, oxidation-reduction potential and metal cations (Wu et al, 2010;Ye et al, 2010). Also the presence of suitable carbon source is necessary to enhance the Cr(VI) reduction capacity (Tekerlekopoulou et al, 2010). Similar observations were also referred in previous studies by Ferro Orozco et al (2010) and Contreras et al (2001).…”
Section: Introductionsupporting
confidence: 51%
“…DNA extraction, PCR amplification, 16S rRNA and 18S rRNA gene sequencing For the isolation of total DNA the method previously described by Tekerlekopoulou et al (2010) was used. The DNA was quantified with a Qubit fluorometer (Invintrogen, USA) according to the manufacturer's instructions.…”
Section: Packed Bed Reactor Experimentsmentioning
confidence: 99%
See 1 more Smart Citation
“…3 Response surfaces: a removal of TOC as a function of the sodium acetate and Cr(VI) concentration; b removal of TOC as a function of the concentration of sodium acetate and ammonium chloride and c removal of TOC as a function of the ammonium chloride and Cr(VI) concentration Cr(VI) was reduced completely at the reactor's effluent. Tekerlekopoulou et al (2010) found that the carbon source is a key parameter for microbial community structure and Cr(VI) reduction. A change of carbon source completely altered the structure of the microbial community from bacteria-dominated to fungus-dominated.…”
Section: Toc Removalmentioning
confidence: 99%
“…Additionally, the presence of a suitable carbon source is necessary to enhance Cr(VI) reduction [31][32][33][34][35][36][37]. As presented in Table 1, numerous different carbon sources have been tested, including glucose, fructose, sodium acetate, lactose, maltose, etc.…”
Section: Introductionmentioning
confidence: 99%